Introduction to the Thematic Feature: International Management Research and Africa: Contents, Tensions, and Cross-Fertilizations - Seny Kan, Konan; Mbengue, Ababacar; Biga-Diambeidou, Mahamadou; ogilvie, dt (Management international / International Management / Gestiòn Internacional, 2022)
This article shows how international business/management (IB/IM) research can be articulated to an in-depth understanding of Africa to serve both academic knowledge development and African priorities. It critically recalls the central characteristics of IB/IM as a field of research, shows how Africa is studied in this field, suggests “African management” as one response to some of the major criticisms of current research in IB/IM, outlines some crossovers between IB/IM and African management, and discusses the contribution of Africa-focused publications in the journal International Management to some of the foundations of the proposed cross-fertilization between IB/IM and African management.